Practicality of Mathematic Learning Material Based on Sway 365 for Sixth Grade Primary School Students - Yola Monica Efriani; Alwen Bentri; Urvi Ghosh (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This research is development research that aims to reveal the practicality level of Microsoft Sway 365-based mathematics teaching materials for sixth-grade elementary school students. For the research instruments, we used questionnaire sheets to measure students’ and teachers’ responses in terms of the practicality of the developed material. The subject of the study was a fourth grader of SD Plus Marhamah. The results suggested 4.23 and 4.4 practicality scores from students and teachers, respectively, categorized as excellent. So, it can be decided that Microsoft sway 365-based mathematics teaching materials are practical to be used for sixth-grade elementary school students